Count and formula: Anclajes of memory in the last twenty-five years (Anclajes, 2021)
Memory and testimony studiesrenew classic debates that confront established theses on the violence of the 20th century. In this framework, I read the critical itinerary of Anclajes as it expands the literary canon from a corpus cut out by the memoirs in conflict in the Southern Cone. Iargue that memoirs are not involved as a remnant of anecdotes of a defeat, but that they emerged in the very center of literary production as a divergent corpus that illuminates a new point of conflict in the colonial dispute over language, writing and territory.
Keywords: memory; testimony; corpus; Argentina; XXI century